PROBLEMATIKA DAN UPAYA HAKIM MEDIATOR DALAM MENDAMAIKAN PERKARA PECERAIAN DI PENGADILAN AGAMA KOTA MALANG (Studi Kasus di Pengadilan Agama Kota Malang 2019) - Budiman Sanusi; Azhar Haq; Nur Hasan (Jurnal Hikmatina, 2020)
AbstractThis research is intended to study the process and implementation of mediation in the Malang City Religious Court. The subject of the debate from this research is what problems are faced by the judge in seeking peace towards the parties and what efforts are made by the judges in the Malang City Religious Court starting from the problems raised by research seeking research under several sub-examples namely : 1) What is the process of conducting mediation in the Malang City Religious Court? (2) What are the problems of the judge in conducting the mediation of divorce cases in the Malang City Religious Court without success? (3) Doing mediator judge efforts in conducting mediation in Malang City Religious Court?In accordance with the above title, this study is included in the category of field research (field research). While the nature of this research is descriptive-analytic, namely describing the discussion material coming from various sources for later analysis carefully in order to obtain results as a result of the study. The license used is juridical based on the applicable laws in Indonesia (positive law). In analyzing the data obtained using qualitative data analysis, after the data collected were analyzed using the deduction method, namely by using the process obtained from general truth.Based on observations during the Malang City Religious Court, in reconciling the parties to be reconciled until now it has been running omtimal because there are other problems such as, problems that need to be by the mediator Judge as for the number of mediators in the Malang Religious Court as many as 23 people and the number of cases approved by the panel of judges per day totaling 50 or more cases a day if one month reaches 1,500 cases then it is certainly difficult for the mediating judge to maximize fully mediated cases, and issues related to the negotiating parties first and are reconciled by their respective parents so the mediator is rather difficult to reconcile the two sides.Key Words: Mediation, Mediator, Role of Judges